KONSEP PEMAAFAN DALAM HADIS DAN DAMPAKNYA TERHADAP INTERAKSI SOSIAL MAHASISWA UIN SUMATERA UTARA - Naya Nazla Az-Zahra; Husnel Anwar (AL-BAYAN INSTITUTE, 2025)
Forgiveness is a trait that everyone must have, so it will make it easier for fellow humans to live a safe and peaceful life. The purpose of this study is to identify the concept of forgiveness in the hadiths of the prophet, as well as the implementation of the value of forgiveness in the social interactions of UIN North Sumatra students, and the effect of mutual forgiveness on the harmony of the student's social environment. This research uses qualitative research with descriptive methods. With research techniques through interviews, documentation and analyzing in depth. The results of this study indicate that UIN North Sumatra students feel the impact of forgiveness on their interactions between students, which makes the heart more relieved, there is no dispute that results in the destruction of friendships, and makes the mind more positive. So that the conclusion of this study, that this forgiveness has begun to be applied by students of UIN North Sumatra, and makes students of UIN North Sumatra more harmonious campus environment among students